Fenomena Beauty Privilege di Kalangan Gen Z - Heriyani, Eka; Lestari, Melina; Gahana, Nibras Mutiara; Azizah, Miwa Nur; Handayani, Varas Kayla; Aisy, Nabila Rihadatul (Pusat Kajian Bimbingan dan Konseling FIPPS Unindra, 2025)
The purpose of this research is to find out how the influence of the Beauty privilege trend among gen Z on female students in one of the private high schools in Jakarta. This research uses a qualitative method through a descriptive study approach, where the existing data is obtained in real terms and in accordance with the situation and conditions when the research is conducted. Of the many students available, sampling was taken totaling 5 female students using the interview method. The results showed that the negative effects of beauty privilege made female students less confident. Based on the results of the research, the counseling teacher will help students to become confident again by making routine language month activities. In addition, BK teachers can also conduct individual counseling to these students and help increase their self-confidence again.